AESTHETICS OF GLAMOR IN THE DESIGN OF MODERN MEN’S SUIT: SEARCH FOR NEW FIGURATIVE AND STYLISTIC SOLUTIONS - Budiak, Viktoriia; Yermakova, Tetiana; Tokar, Maryna (Theory and practice of design, 2024)
Design is characterized by the influence of various social and cultural phenomena and their conceptual embodiment, in particular in costume. Glamor is one of the most expressive phenomena of our time, the massive interest in which is primarily due to fashion trends. Articles of clothing as carriers of visual identification of glamor are associated with typical figurative and associative characteristics, means of shaping, principles of decorative solutions, and the structural organization of the costume form in general. A retrospective analysis of the patterns of formation of the glamor style in clothing demonstrates the path of original formal and constructive transformations, is perceived as a metaphor for the artistic representation of human appearance and indicates the increasing role of the stylizing function of the costume. Purpose. The purpose of the study is to identify the stylistic and formative manifestations of glamor in modern men’s costume. Methodology. The study uses a comprehensive and systematic approach. The analysis of the processes of formation and development of glamor as a phenomenon and style of dress was based on an interdisciplinary approach and a comparative analysis of scientific historical, cultural and art historical sources. The general theoretical and systemic-historical approaches made it possible to trace the evolution of the glamor style in men’s costume. The method of figurative and stylistic analysis was applied to the study of the features of glamorous samples. Thanks to this, the objectively existing practice of borrowing and retrospecting images, structures, cutting techniques, principles of shaping in the interpretation of glamor as a leading conceptual direction in the practice of contemporary design was established. Using the method of typologization, the structures and typologies of glamorous men’s costume images are revealed. Results. The conducted research makes it possible to determine the most characteristic structural and figurative-stylistic features of the formation of a glamorous men’s suit to design promising forms of modern clothing in the style of glamor. The scientific novelty of the research results is that for the first time a holistic scientific approach has been proposed that theoretically substantiates the processes of glamorization of men’s fashion and the search for new figurative and stylistic solutions. The practical significance of the work lies in the fact that the content of the analytical part of the study and its main results can be used in the professional training of designers in the higher education system of Ukraine to improve the quality of design and artistic solutions in the process of developing fashion collections that meet the aesthetic needs of contemporaries.